2011
DOI: 10.1074/jbc.m110.189118
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of the 5′-Untranslated Region Stem-Loop Structure Inhibits α1(I) Collagen Expression in Vivo

Abstract: Type I collagen is a heterotrimeric extracellular matrix protein consisting of two ␣1(I) chains and one ␣2(I) chain. During liver fibrosis, activated hepatic stellate cells (HSCs) are the major source of the type I collagen that accumulates in the damaged tissue. Expression of ␣1(I) and ␣2(I) collagen mRNA is increased 60-fold compared with quiescent stellate cells and is due predominantly to post-transcriptional message regulation. Specifically, a stem-loop structure in the 5-untranslated region of ␣1(I) coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 59 publications
0
33
0
Order By: Relevance
“…To this end, we utilized MEFs derived from knock-in mice in which the 5ЈSL of collagen ␣1(I) mRNA was mutated (denoted here 5ЈSL Ϫ/Ϫ MEFs) (36). Immunoprecipitation with antivimentin antibody using extracts from wild-type (5ЈSL ϩ/ϩ ) MEFs pulled down collagen ␣1(I) and ␣2(I) mRNAs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To this end, we utilized MEFs derived from knock-in mice in which the 5ЈSL of collagen ␣1(I) mRNA was mutated (denoted here 5ЈSL Ϫ/Ϫ MEFs) (36). Immunoprecipitation with antivimentin antibody using extracts from wild-type (5ЈSL ϩ/ϩ ) MEFs pulled down collagen ␣1(I) and ␣2(I) mRNAs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Experiments were performed at cell passages 4 to 9 under serum-free conditions using a 1:1 mixture of Dulbecco's modified essential medium (DMEM) and F-12 nutrient solution (Invitrogen). Mouse embryonic fibroblasts (MEFs) from 5Ј stem-loop mutant (5ЈSL Ϫ/Ϫ ) or wild type (WT) C57/BL6 mice were obtained as previously described (7). The 5ЈSL Ϫ/Ϫ MEFs contained a 21-nt mutation in the 5Ј-UTR of the COL1a1 gene, which disrupted formation of the stem-loop structure, inhibited LARP6 binding, but did not affect the coding region of the COL1a1 gene (7,10).…”
Section: Methodsmentioning
confidence: 99%
“…Mouse embryonic fibroblasts (MEFs) from 5Ј stem-loop mutant (5ЈSL Ϫ/Ϫ ) or wild type (WT) C57/BL6 mice were obtained as previously described (7). The 5ЈSL Ϫ/Ϫ MEFs contained a 21-nt mutation in the 5Ј-UTR of the COL1a1 gene, which disrupted formation of the stem-loop structure, inhibited LARP6 binding, but did not affect the coding region of the COL1a1 gene (7,10). MEFs were cultured in 10% FCS, DMEM, and experiments were performed at passages 4 to 8.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human LARP6 regulates the synthesis of collagen a1(I), a2(I), and likely a1(III) chains via a specific interaction with a unique stem-loop structure in the 59 UTR of these mRNAs that includes the initiation codon and is conserved throughout vertebrates (Cai et al 2010a,b). Recent work has shown that HsLARP6 coordinates the translation of the a1(I) and a2(I) collagen chains as well as their correct assembly, by colocalizing collagen mRNAs with intracellular nonmuscle myosin filaments whose association with polysomes controls the synthesis of heterotrimeric type I collagen (Cai et al 2010a,b;Parsons et al 2011).…”
Section: Introductionmentioning
confidence: 99%